PROFIL PROTEIN TIGA JENIS DAGING YANG DILUMURI SERBUK BUAH MENGKUDU BERBASIS SDS-PAGE - Wa Ode Jariah M; Sri Darmawati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Noni contains protease enzymes that can hydrolyze proteins by breaking the peptide bond, so it can be used to soften the meat. The purpose of this study was toanalyze protein profile on 3 types of meat (goats, buffalo and cow) before and aftergreased with non-fertilizing powder with 30 minutes immersion. Protein profile of three meat types was analyzed using the SDS-PAGE method. The design of this research is descriptive research with the object of research are goat meat, buffalo and cow greased with powder of noni. The results showed that in control meat (goats, buffalo and cow) that were not greased with noni powder there were many major protein bands compared with minor protein bands. While on goat meat, buffalo and cow greased with powder of noni with concentration 10% b / b, 15% b / b, 20% b / b and 25% b / b showed different results at each concentration that there were many minor protein bands than the major protein bands. The higher concentration powder of Noni then the amount of protein in the meat is more denatured. Based on these results indicate that the protease enzyme contained in the powder of noni is able to break peptide bonds in meat protein to proteinshaped minor bands (micromolecul).Keyword : meat, noni powder, protein profile, SDS-PAGE